Remembering partition: Violence, nationalism, and history in India - Pandey, Gyanendra (Cambridge University, 2013)
Gyan Pandey's book is a compelling examination of the violence that marked the Partition of India and how it is remembered. It is also a critique of history-writing and nationalist myth-making. This is a book for historians of South Asia, sociologists, and all those concerned with the Indian subaltern story.